Explaining reduction of pedestrian-motor vehicle crashes in Arkhangelsk, Russia, in 2005-2010 - Kudryavtsev, Alexander Valerievich; Nilssen, Odd-Ragnar; Lund, Johan; Grjibovski, Andrej; Ytterstad, Børge (International Journal of Circumpolar Health, 2012)
Objective. To explain a reduction in pedestrianmotor vehicle crashes in Arkhangelsk, Russia, in 20052010. Study design. Retrospective ecological study. Methods. For 20052010, police data on pedestrianmotor vehicle crashes, traffic violations, and total motor vehicles (MVs) were combined with data on changes in national road traffic legislation and municipal road infrastructure. Negative binomial regression was used to investigate trends in monthly rates of pedestrian motor vehicle crashes per total MVs and estimate changes in these rates per unit changes in the safety measures. Results. During the 6 years, the police registered 2,565 pedestrianmotor vehicle crashes: 1,597 (62%) outside crosswalks, 766 (30%) on non-signalized crosswalks, and 202 (8%) on signalized crosswalks. Crash rates outside crosswalks and on signalized crosswalks decreased on average by 1.1% per month, whereas the crash rate on non-signalized crosswalks remained unchanged. Numbers of signalized and non-signalized crosswalks increased by 14 and 19%, respectively. Also, 10% of non-signalized crosswalks were combined with speed humps, and 4% with light-reflecting vertical signs. Pedestrian penalties for traffic violations increased 4-fold. Driver penalties for ignoring prohibiting signal and failure to give way to pedestrian on non-signalized crosswalk increased 7- and 8-fold, respectively. The rate of total registered drivers’ traffic violations per total MVs decreased on average by 0.3% per month. All studied infrastructure and legislative measures had inverse associations with the rate of crashes outside crosswalks. The rate of crashes on signalized crosswalks showed inverse associations with related monetary penalties. Conclusions. The introduction of infrastructure and legislative measures is the most probable explanation of the reduction of pedestrianmotor vehicle crashes in Arkhangelsk. The overall reduction is due to decreases in rates of crashes outside crosswalks and on signalized crosswalks. No change was observed in the rate of ...